Counterproductive Work Behaviour Among Academic and Administrative Staff and Its effect on the Organizational Effectiveness. - Nevins-Bennett, Cerease Gillian (Advances in Social Sciences Research Journal, 2016)
This article examines the impact of counterproductive work behaviours of academic and administrative staffs on the effectiveness of an educational institution. Results showed that the perpetrators of deviant acts were individual actors and groups who were influenced by personal and organizational factors. Employee behaviours were intentional and geared towards harming the institution for personal benefits and reprisal. These intentional behaviours were targeting specific victims such as the institution, students, other key stakeholders, and the community. The nature and execution of behaviours were divided into categories stemming from misuse of organization’s time and resources, poor attendance and work quality, and unfair work practices. Consequences of these deviant acts led to organizational ineffectiveness in the form of poor students’ services, quality control issues, low students’ intake and retention, and bad institutional reputation - leading to the conclusion that the institution is toxic and not functioning according to it guiding principles and norms.